Haemophilus influenzae invasive disease in children – preliminary results from the Portuguese Study Group - Bajanca-Lavado, Maria Paula (2016)
Introduction: Haemophilus influenzae (H. influenzae) can cause life-threatening infections especially in children. Although six capsular serotypes (a-f) have been identified to date, H. influenzae serotype b (Hib) has long been a major cause of morbidity and mortality. The Hib conjugate vaccine was introduced in the Portuguese Immunization Program in June 2000 and lead to a dramatically decrease of invasive disease. The National Reference Laboratory for Bacterial Respiratory Infections, based at the National Institute of Health in Lisbon, is the reference laboratory for H. influenzae. In the beginning of 2010, the Pediatric Infectious Disease Society and our Laboratory started a surveillance study on invasive H. influenzae infections in paediatric age, with the participation of 30 Hospitals all over Portugal. Material and Methods: From January 2010 to December 2012 we received 28 strains from patients under 18 years old. Twenty-four strains were isolated from blood, three from cerebrospinal fluid, and one from a net joint fluid. Twenty two isolates (78.6%) were from pre-school children (≤5 years old). Males accounted for 78.6% of the cases. β-lactamase production was determined with nitrocefin. Minimum inhibitory concentrations (MIC) was determined for 13 antibiotics by a microdilution assay, according to CLSI guidelines. Serotyping was performed by PCR. MLST was performed for strains isolated after 2011. Results and Discussion: Serotype characterization showed that the majority of the cases (75%) were due to non-capsulated strains (NC). Of the 7 capsulated strains, five were serotype b (two vaccine failures) and two serotypes a and f respectively. Two strains were β-lactamase producers (7.1%). All other strains were susceptible to all antibiotics tested, except for trimethoprim-sulfamethoxazole with 22.2% of resistance. According to other studies MLST also revealed a great diversity among NC strains: 8 different STs in 11 strains. Comparing the results of this surveillance with our first studies, in pre-vaccine era, we are facing a change in the epidemiology of H. influenzae invasive disease with NC, fully susceptible strains, being responsible for invasive disease in Portugal.